Red Ginseng Extract Attenuates Kainate-Induced Excitotoxicity by Antioxidative Effects. (23rd October 2012) - Han, Jin-Yi; Ahn, Sun-Young; Oh, Eun-Hye; Nam, Sang-Yoon; Hong, Jin Tae; Oh, Ki-Wan; Lee, Mi Kyeong
Abstract : This study investigated the neuroprotective activity of red ginseng extract (RGE, Panax ginseng, C. A. Meyer) against kainic acid- (KA-) induced excitotoxicity in vitro and in vivo . In hippocampal cells, RGE inhibited KA-induced excitotoxicity in a dose-dependent manner as measured by the MTT assay. To study the possible mechanisms of the RGE-mediated neuroprotective effect against KA-induced cytotoxicity, we examined the levels of intracellular reactive oxygen species (ROS) and [Ca 2+ ] i in cultured hippocampal neurons and found that RGE treatment dose-dependently inhibited intracellular ROS and [Ca 2+ ] i elevation. Oral administration of RGE (30 and 200 mg/kg) in mice decreased the malondialdehyde (MDA) level induced by KA injection (30 mg/kg, i.p.). In addition, similar results were obtained after pretreatment with the radical scavengers Trolox and N, N ′-dimethylthiourea (DMTU). Finally, after confirming the protective effect of RGE on hippocampal brain-derived neurotropic factor (BDNF) protein levels, we found that RGE is active compounds mixture in KA-induced hippocampal mossy-fiber function improvement. Furthermore, RGE eliminated 1, 1-diphenyl-2-picrylhydrazyl (DPPH) radicals, and the IC50 was approximately 10 mg/ml. The reductive activity of RGE, as measured by reaction with hydroxyl radical ( OH), was similar to trolox. The second-order rate constant of RGE for OH was 3.5–4 .5 × 10 9  M −1 · S −1 . Therefore, these results indicate that RGE possesses radical reduction activity and alleviates KA-induced excitotoxicity by quenching ROS in hippocampal neurons.